Retirement Decisions and Family Characteristics in Costa Rica - Brenes Camacho, Gilbert (2018)
Objective. The coverage of pension plans in Latin America is relatively low and so, people postpone retirement and decide to continue working. The aim of the paper is to analyze the family characteristics that predict the decisions of leaving the job market with or without pension benefits. Methodology. Data from CRELES, a longitudinal survey of the elderly with two cohorts were used. Results and conclusions. Among people aged 55 and older who were working at the baseline, 25% left the labor market, and 9% started receiving retirement money, even though some of them continued working. People who make informal cash transfers to family members are more likely to retire, especially earlier than others. Those who looked after children were more likely to stop working without a formal pension. There was no evidence that the spouse’s working status was related to retirement decisions.